Determinants of family Takaful demand / Abdul Shukor Che Abdullah - Che Abdullah, Abdul Shukor (Faculty of Business and Management, 2010)
The growth of Takaful industry in Malaysia had shown an astonishing performance, from the beginning of Takaful industry until 2010, there were 12 Takaful operators in Malaysia including 4 new Takaful operators who were recently given licence by Bank Negara Malaysia. The Takaful industry has a huge potential to be emphasized especially on their family Takaful. Understanding the factors that influence family Takaful is important to determine the opportunity and chances that can be use to capture full potential growth in the industry. To summarize the research questions, this study undertakes to identify the relationship between the demands for family Takaful and a set of theoretical identified independent variables namely price, inflation, income and level of education. This study also sets out three objectives which in line with the purpose of this study. The first objective is to determine whether the economic indicators chosen inflation and price have relationship between the demands for family Takaful. The second objective is to investigate whether the demand for family Takaful is affect by the demographic factor namely income per family. Finally, this study aim to examine whether the demographic factor namely level of education has any effect towards demand for family Takaful. In this research, it uses a convenient sampling with 50 respondents answering the questionnaire. After that, findings and analysis is process through the SPSS software. As a results, only inflation to have a strong impact to the demand of family Takaful. While, the other factors such as price and income have a moderate relationship with income. Last but not least, level of education insignificantly affects the demand for family Takaful.